Gastrointestinal somatostatin: extraction and radioimmunoassay in different species. Issue 7 (July 1978) - McIntosh, C; Arnold, R; Bothe, E; Becker, H; Köbberling, J; Creutzfeldt, W
Abstract : A radioimmunoassay capable of detecting 300 fg somatostatin has been developed and levels of the polypeptide in gastrointestinal tissues from man, dog, and rat have been measured. Rapid freezing of collected samples and careful control of extraction is necessary. Concentrations in different regions of dog antrum (425 +/- 50 to 773 +/- 254 ng/g tissue) are similar to those in antrum from duodenal ulcer patients and control subjects: 614 +/- 125 and 465 +/- 104 ng/g tissue respectively. Levels in histologically normal human pancreas (253 +/- 43 ng/g tissue) are comparable with those in dog pancreas (333 +/- 66 ng/g tissue), whereas in two cases of neonatal hypoglycaemia the concentration exceeded 3000 ng/g tissue. On gel chromatography the majority of immunoreactive somatostatin elutes as the synthetic tetradecapeptide and a small fraction as a larger species.